"Lacking in Respect for Whitemen": "Tropical Africans" on the Witwatersrand Gold Mines, 1903–1904. (18th November 2014) - Cobley, Alan
Abstract: In May 1903, 380 Africans were recruited from British Central Africa (modern Malawi) by the Witwatersrand Native Labour Association on one-year contracts to work in the gold mines. It was an experiment designed to test the potential for recruiting cheap black labor for the mines from the region north of the Zambesi. By the end of the contract period, more than a quarter of the men were either dead or permanently disabled. Their struggles to adapt to the harsh working conditions in the mines fueled a racist discourse among white South Africans about "Tropical Africans, " which focused on their supposed susceptibility to disease on the one hand, and their supposed "natural indolence" on the other. Notwithstanding these issues, the mine owners considered the experiment a success and moved rapidly to expand recruitment from the region in the years that followed. This article tells the story of this pioneering group of migrant workers, detailing their grim encounter with modernity and the power of capital in South Africa. It also suggests ways in which their experiences helped to determine the conditions of employment for the generations of migrant mineworkers that followed them.